On the End of Privacy : Dissolving Boundaries in a Screen-Centric World - Miller, Richard E. (Richard Earl), 1961- (Pittsburgh series in composition, literacy, and culture., 2019)
In preparation for this book, and to better understand our screen-based, digital world, Miller only accessed information online for seven years. On the End of Privacy explores how literacy is transformed by online technology that lets us instantly publish anything that we can see or hear. Miller examines the 2010 suicide of Tyler Clementi, a young college student who jumped off the George Washington Bridge after he discovered that his roommate spied on him via webcam. With access to the text messages, tweets, and chatroom posts of those directly involved in this tragedy, Miller asks: why did no one intervene to stop the spying? Searching for an answer to that question leads Miller to online porn sites, the invention of Facebook, the court-martial of Chelsea Manning, the contents of Hillary Clinton's email server, Anthony Weiner's sexted images, Chatroulette, and more as he maps out the changing norms governing privacy in the digital age.